Human Development in Poor Countries: On the Role of Private Incomes and Public Services. - Anand, S; Ravallion, M (American Economic Association, 1993)
Development is often taken to mean rising incomes. Discussions of the "goals of development" now often emphasize the reduction of poverty, rather than raising average incomes per se. The role of social services—particularly basic health and education—has also received greater emphasis in the 1980s, viewed mainly as instruments for raising the incomes of the poor. But, in all these approaches, income growth of one sort or another is what development is all about. A rather different view of the meaning of development has recently found expression in the 1990 Human Development Report (HRD) produced by the United Nations Development Programme. A conceptual underpinning for this approach can be found in the work of Amartya Sen. The essence of this view is that human development—what people can actually do and be—is the overriding purpose of economic development. Underdevelopment is viewed as the lack of certain basic capabilities, rather than lack of income per se. We do not aim here to advocate one of these approaches over the other, but rather to explore their implications for development policy. For instance, what does the human development approach imply about the role of economic growth and, in particular, about reducing income poverty? Should development priorities shift toward the provision of public services in poor countries, even if such a shift is at the expense of income growth?